HUBUNGAN ANTARA PROFESIONALISME GURU PAI DENGAN INTENSITAS IBADAH SISWA SMA NU JUNTINYUAT KABUPATEN INDRAMAYU - Zamzami, Zamzami; Rokhman, Asep Saepul (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2021)
In educational activities at school, a teacher is the spearhead of success in teaching and learning activities. So, he is required to be professional. Mohamad Surya states in the Draft Law on Teachers (article 14) that: